Design and Construction of Electrical Magnate to Study its Efficiency and the Optimum Parameters to Produce Alkaline Magnetic Water and Treating the Sea Water to be Suitable for Irrigation - Al-Bayati, Alaa Dhari Jawad (Al-Khwarizmi Engineering Journal, 2015)
Abstract Electrical magnate was designed and constructed, the optimum Magnetic flux and the effect of time on the physical properties of the alkaline (magnetic water) produced from the bottled drinking water [the total dissolved solids (TDS) or the electrical conductivity, and pH] were studied, to simulate ZamZam water in Mekka Saudi Arabia. Also, the efficiency of magnetic field from this designed electrical magnate in decreasing the TDS of sea water (of 1500 ppm NaCl Content), to convert it to water suitable for irrigation (TDS<1000 ppm) was investigated in this work.The results show that the magnetic flux from our designed electrical magnate in the range of (0.013- 0.08) Tesla and 30 minutes magnetic treatment time is sufficient to produce alkaline water with pH similar to ZamZam water (pH from 7.85- 8). While 60 minutes of magnetic treatment results to higher values of pH and the maximum pH value of 8.9 is obtained when the magnetic flux is 0.026 Tesla. The investigation for reducing the TDS of water having 1500 ppm NaCl show that , the maximum decrease in TDS is took place when the magnetic flux is 0.013 Tesla(coil of 100 turn and 1.5 V) and the time for magnetic treatment is 30 minutes where the TDS of 1730 ppm reduced to 1290 ppm is obtained .The effect of magnetic treatment on the pH change of high NaCl content water give maximum pH value of 8.1 when the magnetic flux is 0.013 and 0.028 Tesla (the voltages is 1.5 & 3 V respectively and 100 turn coil) and the time period of magnetic treatment is 30 minutes. The trend of results agreed well with previous studies, where the magnetic treatment lead always to increase of pH, decrease in TDS and electrical conductivity Keywords: Electrical magnate, Magnetic water, alkaline water, Design of electrical magnate, TDS, pH, ZamZam water.